Novel material from immobilization of magnesium oxide and cetyl trimethyl ammonium bromide nanoparticles onto waterworks sludge for removing methylene blue from aqueous solution - Hayder M. Rashid; Mohammed B. Abdul-Kareem; Salim H. Jassam; Waqed H. Hassan; Ayad A.H. Faisal; Ayman A. Ghfar; Nadhir Al-Ansari (Journal of King Saud University: Science, 2023)
Utilizing the waterworks sludge byproduct in the treatment of wastewater contained methylene blue dye is one approach that has been taken in an effort to lessen the difficulties that are associated with managing such byproduct. The prime aim of this work is manufacturing of novel sorbent from co-precipitation of magnesium oxide nanoparticles on the surfaces of waterworks sludge in the existence of cetyl trimethyl ammonium bromide surfactant. Surfactant 0.04 g/50 mL, dose of sludge 2 g/50 mL, and pH 12 were the most efficient preparation parameters to remove 75.31% of adopted dye. The adsorption studies were conducted under various conditions of contact time (0–240 min), concentration of dye (10–300 mg/L), sorbent mass (0.05–1.5 g), and solution pH (3–12). The best values of batch parameters were identical to the highest percentages of contaminant removal. Results proved that the magnesium oxide nanoparticles are attached to the sludge surfaces. Freundlich and pseudo-second-order models have perfectly described sorption results with 59.92 mg/g maximum sorption capacity. The breakthrough curves can be accurately described by the Bohart-Adams model. The outputs of continuous tests have been paved the way for future usage of the prepared sorbent in the field permeable reactive barrier technology.